2005
DOI: 10.2202/1538-0645.1448
|View full text |Cite
|
Sign up to set email alerts
|

A Test for Collusion between a Bidder and an Auctioneer in Sealed-Bid Auctions

Abstract: This paper derives a regression-based test to detect bidder-auctioneer cheating in sealed bid auctions. I apply this regression test to data from the New York City School Construction Authority auctions, an approximate one billion dollar per year auction market in which an auctioneer engaged in bidder-auctioneer cheating. Using the regression analysis to compare lots where bid rigging occurred with certainty to all other auctions allows one to conclude that bidder-auctioneer cheating significantly distorted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Feinsten et al (1985) studied North Carolina highway contracts and found that non-competitive bidding led to a clustering of bids in an attempt to influence engineer's estimates of the cost of future lettings. Ingraham (2005) considered the possibility of bidder-official collusion in contracting and examined bidder data from New York City School Construction Authority auctions relating to school repair and construction for the period 1990-1997. In April 1993 a scandal relating to bid rigging became public and a number of prosecutions ensued: officials in the School Construction Authority colluded with contractors by operating a "magic-number" scheme.…”
Section: The Construction Industrymentioning
confidence: 99%
“…Feinsten et al (1985) studied North Carolina highway contracts and found that non-competitive bidding led to a clustering of bids in an attempt to influence engineer's estimates of the cost of future lettings. Ingraham (2005) considered the possibility of bidder-official collusion in contracting and examined bidder data from New York City School Construction Authority auctions relating to school repair and construction for the period 1990-1997. In April 1993 a scandal relating to bid rigging became public and a number of prosecutions ensued: officials in the School Construction Authority colluded with contractors by operating a "magic-number" scheme.…”
Section: The Construction Industrymentioning
confidence: 99%
“…As for the corruption scheme, our study is related to models where the favored bidder is allowed to revise his bid after the original submission (e.g., Compte et al, 2005;Ingraham, 2005;Koc and Neilson, 2008;Wolfstetter, 2004, 2010;Menezes and Monteiro, 2006; and studies related to the right of first refusal). In these models, the favored bidder, if he wishes, will revise his bid such that he can just beat his effective rival and win the auction.…”
Section: Related Literaturementioning
confidence: 99%
“…Procurement auctions are prevalently employed as a powerful appliance that greatly reduces the risk of corruption. However, auctions are still not corruption-proof, since auctioneers "whose salaries are small relative to the prices of the items they auction off" are likely to "enter a bid-rigging scheme in exchange for a sufficient kickback from a dishonest bidder" (Ingraham, 2005). For example, in order to win a turbine contract worth €205.6 million, Siemens paid €2.987 million in bribes to an Italian utility company; a Scottish engineering company paid £3.1 in kickbacks to foreign officials to secure 16 contracts for water treatment equipment worth £34.3 million (OECD/World Bank, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since spacings are increments of the empirical quantile function, our work is related to the rapidly emerging literature on quantile methods in first-price auctions, see Marmer and Shneyerov (2012), Ma et al (2019) for kernel-based estimators, Luo and Wan (2018) for isotone regression-based estimators, and Guerre and Sabbah (2012), Gimenes and Guerre (2021) for local polynomial estimators. More generally, spacings have been used for collusion detection in Ingraham (2005), for set identification of bidders' rents in Paul and Gutierrez (2004), Marra (2020), and in the prior-free clock auction design in Loertscher and Marx (2020).…”
Section: Introductionmentioning
confidence: 99%